The impact of circulating IGF-1 and IGFBP-2 on cardiovascular prognosis in patients with acute coronary syndrome - Wang, Wei; Yu, Kang; Zhao, Shou-Yong; Mo, De-Gang; Liu, Jia-Hui; Han, Li-Jinn; Li, Tai; Yao, Heng-Chen (Frontiers in Cardiovascular Medicine, 2023)
Background: While insulin-like growth factor 1 (IGF-1) exerts a cardioprotective effect in the setting of atherosclerosis, insulin-like growth factor binding protein 2 (IGFBP-2) is involved in metabolic syndrome. Although IGF-1 and IGFBP-2 are known to be predictors for mortality in patients with heart failure, their use in clinic as prognostic biomarkers for acute coronary syndrome (ACS) requires investigation. We evaluated the relationship between IGF-1 and IGFBP-2 levels at admission and the risk of major adverse cardiovascular events (MACEs) in patients with ACS. Methods: A total of 277 ACS patients and 42 healthy controls were included in this prospective cohort study. Plasma samples were obtained and analyzed at admission. Patients were followed for MACEs after hospitalization. Results: Among patients who suffered acute myocardial infarction, plasma levels of IGF-1 and IGFBP-2 were lower and higher, respectively, as compared to healthy controls (both p<0.05). The mean follow-up period was 5.22 (1.0–6.0) months and MACEs incidence was 22.4% (62 of 277 patients). Kaplan–Meier survival analysis revealed that patients with low IGFBP-2 levels had a greater event-free survival rate than patients with high IGFBP-2 levels (p<0.001). Multivariate Cox proportional hazards analysis revealed IGFBP-2, but not IGF-1, to be a positive predictor of MACEs (hazard ratio 2.346, 95% CI 1.321–4.166; p=0.004). Conclusion: Our findings suggest that high IGFBP-2 levels are associated with the development of MACEs following ACS. Moreover, IGFBP-2 is likely an independent predictive marker of clinical outcomes in ACS.